STRUCTURAL VARIABLE ON THE JOB SATISFACTION OF 4 AND 5 STARRED HOTEL EMPLOYEES IN SURABAYA - Agustinus Nugroho; Endo Wijaya Kartika; Thomas Stefanus Kaihatu (Jurnal Manajemen dan Wirausaha, 2014)
The study aimed to find out the effect of management’s controllable factor, which was called internal factor or structural variable, on the job satisfaction of the 4 and 5 starred hotel employees’ in Surabaya. The study used quantitative explanative technique to explain the effect of structural variable on employees’ job sa-tisfaction. The result showed that structural variable had a positive and significant effect on job satisfaction. It is also found that employees’ job satisfaction was high when there was (or the highest indicator for structural variable was) fellow employees’ support and supervisor’s support, while the lowest indicator was job routine; the highest indicator for job satisfaction was satisfaction in salary, while the lowest indicator was supervisor’s competency in performing his or her tasks. The study aimed to find out the effect of management’s controllable factor, which was called internal factor or structural variable, on the job satisfaction of the 4 and 5 starred hotel employees’ in Surabaya. The study used quantitative explanative technique to explain the effect of structural variable on employees’ job sa-tisfaction. The result showed that structural variable had a positive and significant effect on job satisfaction. It is also found that employees’ job satisfaction was high when there was (or the highest indicator for structural variable was) fellow employees’ support and supervisor’s support, while the lowest indicator was job routine; the highest indicator for job satisfaction was satisfaction in salary, while the lowest indicator was supervisor’s competency in performing his or her tasks.